Forecasting the maximum temperatures in Duhok Governorate for the year 2011 Using one of the ARIMA models of the Box-Jenkins theory of time series (Journal of the College of Basic Education, 2023)
This research provides an explanation of the steps of using ARIMA models (ATUO REGRESSIVE Moving Average) to predict the maximum temperatures for the year 2011 in Dohuk Governorate, using the Box-Jenkins theory of time series, and applying the statistical program SPSS (Statgraphics). The range and average were estimated as well. The autocorrelation coefficient for the time series for the period from 2001-2010 and testing it in terms of being stable and after estimating the mean square errors (MSE) (LESSMEANS SQUARE ERORE) and conducting the test for the results, it was found that the model (1,1,0) ARIMA is more suitable for prediction than the model (1,0 Accordingly, the predicted maximum temperatures for Duhok Governorate for the year 2011 were given.